Post-translational regulation and trafficking of the granulin-containing protease RD21 of Arabidopsis thaliana. - Christian Gu; Mohammed Shabab; Richard Strasser; Pieter J Wolters; Takayuki Shindo; Melanie Niemer; Farnusch Kaschani; Lukas Mach; Renier A L van der Hoorn (PLoS ONE)
RD21-like proteases are ubiquitous, plant-specific papain-like proteases typified by carrying a C-terminal granulin domain. RD21-like proteases are involved in immunity and associated with senescence and various types of biotic and abiotic stresses. Here, we interrogated Arabidopsis RD21 regulation and trafficking by site-directed mutagenesis, agroinfiltration, western blotting, protease activity profiling and protein degradation. Using an introduced N-glycan sensor, deglycosylation experiments and glyco-engineered N. benthamiana plants, we show that RD21 passes through the Golgi where it becomes fucosylated. Our studies demonstrate that RD21 is regulated at three post-translational levels. Prodomain removal is not blocked in the catalytic Cys mutant, indicating that RD21 is activated by a proteolytic cascade. However, RD21 activation in Arabidopsis does not require vacuolar processing enzymes (VPEs) or aleurain-like protease AALP. In contrast, granulin domain removal requires the catalytic Cys and His residues and is therefore autocatalytic. Furthermore, SDS can (re-)activate latent RD21 in Arabidopsis leaf extracts, indicating the existence of a third layer of post-translational regulation, possibly mediated by endogenous inhibitors. RD21 causes a dominant protease activity in Arabidopsis leaf extracts, responsible for SDS-induced proteome degradation.